P20 The eligibility of patients with difficult asthma for omalizumab since the change to the treatment criteria. (16th November 2010) - Burton, AJ; Hargadon, B; Murphy, AC; Brightling, CE; Pavord, ID; Wardlaw, AJ; Bradding, P; Green, RH
Abstract : Omalizumab is a humanised monoclonal anti-IgE agent which is useful as an add-on therapy for severe atopic asthma. We have previously shown that 13.5% of patients attending our adult difficult asthma clinic were eligible for treatment with omalizumab. There has recently been a change to its prescribing licence with a widening of the eligible range of IgE from 30–700 iu/ml to 30–1500 iu/ml. Other prescribing criteria are (1) weight between 20 and 150 kg, (2) FEV1 <80% predicted, (3) positive skin prick tests or specific IgE to perennial aeroallergens and (4) ongoing symptoms despite a high-dose combination inhaler. In addition NICE guidance now recommends that its use is confined to patients who, within the past year, have had two or more hospital admissions or one admission plus two A&E attendances for asthma exacerbations. We aimed to determine how the new licensing criteria and the NICE guidelines have affected the proportion of patients attending our difficult asthma clinic eligible for treatment with omalizumab. We assessed 510 patients recording body weight (kg), FEV1 (% predicted), symptoms, total IgE (iU/ml) and skin prick tests. Our data demonstrate that 240 had an IgE outside the eligible range, 242 patients had an FEV1 >80%, 46 patients had negative skin prick tests and a further 2 patients′ weight was outside the range for dosing. 67/510 (13.1%) patients met all the licensing criteria for omalizumab. There has therefore not been any increase in the proportion of eligible patients since the widening of the IgE range. Of these 67, 27 patients had two or more admissions with asthma exacerbations in the previous year. A further 16 patients had one admission but less than 2 A&E attendances. 12 patients required maintenance oral prednisolone but did not have sufficient admissions to meet the NICE prescribing guidelines. In total, 27/510 (5.3%) of patients with difficult-to-treat asthma were eligible for treatment with omalizumab according to NICE guidance. Although omalizumab is a helpful additional therapy for allergy-mediated asthma, its licensing criteria and current NICE guidelines limits its use in the UK to a small proportion of patients with difficult asthma.